Transnational feminism in film and media - Marciniak, Katarzyna, 1963-; Imre, Anikó; O'Healy, Áine (Comparative feminist studies series, 2007)
This collection of interdisciplinary essays examines current cinematic and media landscapes from the perspective of transnational feminist practices and methodologies. Focusing on film, media art, and video essays, the contributors chart innovative strategies for exploring contemporary visual cultures.